Hubungan Faktor Maternal, Fetal, dan Ketepatan Rujukan dengan Keputusan Sectio Caesarean di Rsud Bangil Periode Januari–Maret 2025 - Anis Puji Rahayu; Diadjeng Setya Wardani; Krisjentha Iffah Agustasari (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: In obstetric emergencies, cesarean section (CS) is a crucial surgical intervention to save both mother and baby. Although the WHO recommends an optimal CS rate of 10–15%, the prevalence of CS at Bangil Regional Hospital has risen sharply to 80% in 2024. This marked deviation from the standard prompted a study to analyze the key factors influencing CS decision-making at the hospital.Objective: To analyze the relationship between maternal factors, fetal factors, and referral accuracy with the decision to perform CS at Bangil Regional Hospital. Methods: This quantitative study employed a cross-sectional design involving 202 women who gave birth during the first trimester of 2025, selected through simple random sampling. Secondary data from medical records were analyzed using the Chi-square test to examine the association between maternal, fetal, and referral variables and the likelihood of undergoing CS. Results: The decision to perform CS was significantly associated with a history of previous CS (p = 0.001), comorbid conditions (p = 0.040), other maternal medical indications (p = 0.041), and fetal distress (p = 0.001). In contrast, maternal age, parity, and referral accuracy showed no significant association. These findings indicate that CS decisions are more strongly influenced by maternal and fetal clinical urgency than by demographic or systemic factors. Strengthening risk detection and optimizing maternal–fetal monitoring are therefore essential to reduce morbidity and mortality.